PROTAGORO RELIATYVIZMAS: FRAGMENTŲ ANALIZĖ. - Čelutka, Simas (Problems / Problemos, 2013)
The article provides an analysis of Protagorean philosophy, concentrating on his famous homo mensura fragment. The examination is supported by significant philological clarifications, which eventually lead to the conclusion that ethico-political relativism does not follow from homo mensura fragment: only perceptual relativism logically follows. The argument goes on to show that Protagorean perceptual relativism may be understood both objectively and subjectively. The Heraclitean and Parmenidean influences upon Protagoras' thought are also indicated. It is consequently shown how Plato and Aristotle misunderstood the central thesis of Protagoras, at the same time retrieving the homo mensura fragment from charges of self-refutation. It is also argued that Protagoras should not be called an "atheist", but only a "subjective agnostic".